The Effects of Processing Fluency in Prosocial Campaigns: Effort for Self-Benefit Produces Unpleasant Feelings - Kim, Yaeeun; Kim, Yaeri (Frontiers in Psychology, 2020)
This study investigates how consumers’ intentions related to prosocial campaigns were accompanied by metacognitive experiences. Two studies examined how the relationship between appeal type (self-benefit vs. social benefit) and the level of processing fluency (easy vs. difficult) influenced attitudes toward prosocial campaigns. The findings revealed that individuals who were manipulated to find self-benefit appeal displayed less favorable attitudes toward disfluent prosocial campaigns than those who were manipulated to find social benefit appeal. The underlying mechanism of this result was that the extra effort invested to understand prosocial campaigns with difficult processing fluency produced unpleasant feelings.